2017
DOI: 10.5812/jjcdc.41340
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sleep Disorders During Pregnancy and

Abstract: Background: Sleep disorder is one of the most common complaints of pregnancy that can lead to maternal and fetal complications. Objectives: The main purpose of this study is to investigate the correlation between sleep disorders of pregnancy and abortion. Methods: This study is conducted using a case-control method on 218 women in the age range of 18 -35 years old with singletonpregnancy passing their first or second pregnancy in Ahvaz, Iran. Continuous sampling was conducted on the basis of characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
2
1
0
Order By: Relevance
“…This study was carried out to examine the relationship between poor sleep quality and related pregnancy outcomes. Findings of this study showed that sleep disturbance is associated with preterm delivery which is in accordance with previous studies ( 16 - 18 ). Okun and colleagues found that the level of interleukin-6 (IL-6) was higher in pregnant women with short sleep duration or poor sleep quality ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
“…This study was carried out to examine the relationship between poor sleep quality and related pregnancy outcomes. Findings of this study showed that sleep disturbance is associated with preterm delivery which is in accordance with previous studies ( 16 - 18 ). Okun and colleagues found that the level of interleukin-6 (IL-6) was higher in pregnant women with short sleep duration or poor sleep quality ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
“…The Mean±SD score of Spiritual Well-Being of the elderly in the present study was high (96.47±13.43) and more than half of the subjects achieved a high Spiritual Well-Being score which is in line with many studies (Anand, Jones & Gill 2015;Adib-Hajbaghery & Faraji 2015;Alihosseini, Najar & Haghighizadeh 2017;Chaves & Gil 2015). Some studies have concluded that religion and spirituality are important sources of strength and support among elderly people, which help them to tolerate critical and stressful situations (Jadidi et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Compared to women in the general population, antenatal women sleepless. [ 1 ] Apart from the physical tiredness that ensues, lack of sleep also leads to mental stress,[ 2 ] hypertension in pregnancy,[ 3 ] postpartum depression,[ 4 ] abortions,[ 5 ] increased inflammatory cytokines,[ 6 ] and preterm babies. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%